FEATURES OF ORGANIZING PROJECT ACTIVITIES IN GOVERNMENT AUTHORITIES - Nigina Sharipova (European Science Publishing, 2025)
Project-based approaches in government authorities have become a critical tool for enhancing efficiency, transparency, and responsiveness. This study examines the distinctive features of organizing project activities in government bodies, focusing on their structures, processes, and outcomes. Data were collected through case studies and surveys, revealing key strategies and challenges. The findings indicate that adopting project management principles can significantly improve public service delivery, despite barriers like bureaucratic rigidity and resource constraints. Evidence from Tashkent State University of Economics’ case-study experience demonstrates the positive impact of structured project activities. Recommendations for policy and practice are provided to facilitate successful implementation.
Keywords: Project management, government authorities, public administration, organizational efficiency, stakeholder engagement, Tashkent State University of Economics, participatory governance.